Oxidative stress in development and neonatal diseases - Dennery, Phyllis (Henry Stewart Talks, 2007)
Cellular effects of oxygen radicals, Sources of ROS, Hyperoxia, ROS in various processes, ROS: good or bad?, Important antioxidants, Antioxidant vitamins, Less traditional antioxidants, HO-1 gene, Nitric oxide, ROS and Down syndrome, ROS contribution to neonatal diseases, Clinical trial with antioxidants in neonates
Archived at 2018/10/28